2020
DOI: 10.1101/2020.11.03.365395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted long-read sequencing resolves complex structural variants and identifies missing disease-causing variants

Abstract: BACKGROUND: Despite widespread availability of clinical genetic testing, many individuals with suspected genetic conditions do not have a precise diagnosis. This limits their opportunity to take advantage of state-of-the-art treatments. In such instances, testing sometimes reveals difficult-to-evaluate complex structural differences, candidate variants that do not fully explain the phenotype, single pathogenic variants in recessive disorders, or no variants in specific genes of interest. Thus, there is a need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The enrichment of targets in human cells (26)(27)(28)(29)(30) or species in mock communities (27,31) or fecal samples of lions ( 32) was previously demonstrated. In the present study, we used clinical metagenomic samples obtained from vaginal swabs of pregnant women to evaluate the performance to deplete the high content of human DNA that heavily impairs downstream microbiome analyses.…”
Section: Discussionmentioning
confidence: 89%
“…The enrichment of targets in human cells (26)(27)(28)(29)(30) or species in mock communities (27,31) or fecal samples of lions ( 32) was previously demonstrated. In the present study, we used clinical metagenomic samples obtained from vaginal swabs of pregnant women to evaluate the performance to deplete the high content of human DNA that heavily impairs downstream microbiome analyses.…”
Section: Discussionmentioning
confidence: 89%
“…Recent work has shown that rare SVs are abundant in human populations 86 , and can be missed even by long-read assembly-based approaches 87 . With improved prioritization schemes, the clinical benefit of long-read sequencing can be maximized relative to its cost 88 . We believe compartmap can serve a key role in facilitating this process for novel SVs, maximizing the value of both existing and new data, thereby accelerating discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…With continuing improvements, long-read technologies can enable sequencing of more such difficult-to-sequence regions, identifying new associations between genomic regions and genetic disorders. Several groups have exemplified the clinical significance of targeted long-read sequencing using CRISPR/Cas9 [114] mediated methods [115,116] or computational adaptive sampling [117] for enrichment of specific regions of the genome. In a small cohort of 22 patients with known canonical and complex SVs, Miller et al [117] demonstrated that targeted LRS can not only detect all SVs previously identified with clinical testing (n = 46) but also discovered variants (n = 41) that were missed by the clinical test.…”
Section: Long-read Sequencingmentioning
confidence: 99%
“…Several groups have exemplified the clinical significance of targeted long-read sequencing using CRISPR/Cas9 [114] mediated methods [115,116] or computational adaptive sampling [117] for enrichment of specific regions of the genome. In a small cohort of 22 patients with known canonical and complex SVs, Miller et al [117] demonstrated that targeted LRS can not only detect all SVs previously identified with clinical testing (n = 46) but also discovered variants (n = 41) that were missed by the clinical test. Targeted long-read sequencing has the potential to be used clinically for patients with suspected complex SVs and tandem repeats in candidate genes.…”
Section: Long-read Sequencingmentioning
confidence: 99%